2023
DOI: 10.1057/s41264-023-00213-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding family takaful purchase behaviour: the roles of religious obligation and gender

Abstract: Takaful is an important and major segment of the finance industry that is poised for growth. Understanding the factors that influence Muslim consumers’ purchasing behaviour is crucial to accelerate the growth in the family takaful market segment. However, research has yet to adequately address the drivers of family takaful purchase behaviour. By integrating religious obligation into the theory of planned behaviour, this study proposed and tested a model of the factors underlying family takaful purchasing behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…This study demonstrated that attitude (Lebdaoui et al , 2022; Pratama et al , 2023; Saygılı et al , 2022), subjective norm (Farhat et al , 2019; Yusfiarto et al , 2023), PBC (Alzadjal et al , 2021; Maduku and Mbeya, 2023), Islamic financial literacy (Muslihun, 2023; Yeni et al , 2023), religiosity (Alharbi et al , 2021; Alzadjal et al , 2021), consumer conformity (Klabi and Binzafrah, 2023), Islamic branding (Dinc et al , 2023; Faiza, 2023) and behavioural intention (Aslam et al , 2022; Wijaya et al , 2023) influence the compliance behaviour of Islamic customers in Islamic banks. The relationship model between attitude variables, subjective norms, PBC, Islamic financial literacy, religion, consumer conformity, Islamic branding and customer sharia compliance behaviour, which is mediated by behavioural intention factors, represents another discovery (Junaidi et al , 2022; Yeni et al , 2023; Alharbi et al , 2021; Muslihun, 2023).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This study demonstrated that attitude (Lebdaoui et al , 2022; Pratama et al , 2023; Saygılı et al , 2022), subjective norm (Farhat et al , 2019; Yusfiarto et al , 2023), PBC (Alzadjal et al , 2021; Maduku and Mbeya, 2023), Islamic financial literacy (Muslihun, 2023; Yeni et al , 2023), religiosity (Alharbi et al , 2021; Alzadjal et al , 2021), consumer conformity (Klabi and Binzafrah, 2023), Islamic branding (Dinc et al , 2023; Faiza, 2023) and behavioural intention (Aslam et al , 2022; Wijaya et al , 2023) influence the compliance behaviour of Islamic customers in Islamic banks. The relationship model between attitude variables, subjective norms, PBC, Islamic financial literacy, religion, consumer conformity, Islamic branding and customer sharia compliance behaviour, which is mediated by behavioural intention factors, represents another discovery (Junaidi et al , 2022; Yeni et al , 2023; Alharbi et al , 2021; Muslihun, 2023).…”
Section: Discussionmentioning
confidence: 73%
“…Alzadjal et al (2021) found that Islamic bank clients’ behaviour is highly influenced by their perception of behavioural control. Maduku and Mbeya (2023) discovered that PBC affects Sharia compliance behaviour in Sharia financial products significantly and positively.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor leading to the lack is that once banks are Islamized, religious considerations must be taken into account in all services. Islamic banks should therefore be able to provide legal assistance to banks and their customers and should have fully Shariah-compliant banking laws 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The idea of takaful is to offer participants financial support in the event of catastrophe based on mutual aid, brotherhood, and solidarity. The Takaful Act (Laws of Malaysia 1984) defines takaful as a system based on fraternity, solidarity, and mutual benefit that provides financial aid to members in need through a procedure where members collectively agree to pay for that purpose (Maduku & Mbeya, 2023).…”
Section: Introductionmentioning
confidence: 99%